Progospodarczy wymiar polityki ekologicznej władz lokalnych - Sztando, Andrzej (Pro-Economic Dimension of Local Governments' Ecological Policy, 2006)
The introductory part of the article is devoted to the presentation of the economic local policy idea. The author presents here its similarities and differences in comparison to the national economic policy, later in the article he creates its definition and identifies the set of its aims. It enables the author to indicate the groups of influence instruments of local authorities on the economic subjects as well as to form nine areas of activity, where they are applied. Further in the article, he defines local ecological policy and its pro-economic area. The article also includes detailed presentation of instruments which belong to this area. It enables the presentation of different concepts referring to the relations between the local economic development and the development of natural environment. It is worth emphasizing, that the author concentrates not only on the differences appearing between the two processes, but he also pinpoints the similarities between the two.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 341-356